Aspectos epidemiológicos da infecção por Leishmania spp. em gatos-domésticos - Hartmann, Gabriela (2023)
Leishmaniasis are a group of chronic diseases, mostly zoonotic, which are among the vector-borne diseases of greatest importance in the global public health context. In all susceptible hosts, these diseases are caused by flagellated protozoa of the genus Leishmania, transmitted mainly through the bite of invertebrate vectors belonging to the subfamily Phlebotominae, with Lutzomyia spp. and Phlebotomus spp. being the most relevant species in the transmission. In veterinary medicine, canine leishmaniasis is the most widely studied due to the dog's role as the main urban reservoir host of L. infantum, the etiological agent of human visceral leishmaniasis, as well as for the importance of leishmaniosis in canine medicine. Cats have always been considered refractory to infection. However, the role of the domestic cat in these pathogens' biological cycle has been questioned due to an increase in feline leishmaniasis case numbers, as well as the published reports of Leishmania spp. infection in this species in the last few years. Thus, the scope of this work was to make a review of feline leishmaniasis and a seroepidemiological screening study using the indirect immunofluorescence antibody test (IFAT) of 389 serum samples from cats submitted to necropsy, to understand whether the cats are being exposed to Leishmania spp., despite that no cases of feline leishmaniosis are known in the study region, regardless of being an area of L. infantum transmission. Epidemiological data of these cats, such as gender, reproductive status, age group, breed, length and coat color/pattern, feline immunodeficiency virus (FIV), and/or feline leukemia virus (FeLV) infection were collected and correlated with IFAT seropositivity. The frequency of anti-Leishmania spp. antibody detection in the tested cats was 11.05% (43/389), with a positive statistical association between seropositivity and coat color within the orange spectrum with wide white parts cats, with p=0.044 and OR=2.47 (1 – 6.13) and a negative association was found concerning FeLV infection, with p=0.01 and OR=0.38 (0.18 – 0.79). No other correlations were found. Therefore, it is possible to conclude that cats are being exposed to Leishmania spp.. Complementary molecular studies will be useful in the future for differentiating between exposure and active infection in these cats. Additionally, it is expected that the described data will be helpful in the diagnostic routine of veterinary clinicians and pathologists, promoting awareness regarding the disease, its pathogenesis and associated lesions/clinical manifestations, as well as the diagnostic pathways, treatment, and prevention, due to feline leishmaniasis being an emerging disease worldwide.